Опасные профессии: Книга для смелых мальчишек / [Гэзлей С., Дрейер Д., Хоппинг Л. Дж. - Гэзлей С. (Росмэн, 2008)
Экземпляры: Ч/з ДБ (20090427) / Инвентарный номер: 94439 / Цена: 207.90 / Авт.знак: Г 99 / ГРНТИ: 14 / ББК: 92я2